2010
DOI: 10.1017/s0950268810002645
|View full text |Cite
|
Sign up to set email alerts
|

Detecting new and emerging diseases on livestock farms using an early detection system

Abstract: The monitoring and surveillance of animal diseases is becoming increasingly important to policy-makers in Great Britain particularly given recent incursions of avian influenza and the emergence of bovine spongiform encephalopathy. To meet this surveillance objective, data from British livestock is collected and analysed retrospectively on an ongoing basis. However, these data can also be analysed prospectively within an early detection system which raises alerts to significant increases in disease reporting so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Since 2002, a system for monitoring and surveillance of animal diseases has been developed in the Netherlands to rapidly detect emerging diseases, 7,27 which is of utmost importance to government and livestock policy makers as well as the livestock industry. 6,22 The sudden, frequent occurrence of stillborn malformed lambs and calves in December 2011 eventually resulted in the association between the arthrogryposishydranencephaly syndrome and the recently discovered SBV. Until that moment, SBV was associated with an unidentified disease, affecting dairy cattle in the Netherlands and Germany, Figure 11.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2002, a system for monitoring and surveillance of animal diseases has been developed in the Netherlands to rapidly detect emerging diseases, 7,27 which is of utmost importance to government and livestock policy makers as well as the livestock industry. 6,22 The sudden, frequent occurrence of stillborn malformed lambs and calves in December 2011 eventually resulted in the association between the arthrogryposishydranencephaly syndrome and the recently discovered SBV. Until that moment, SBV was associated with an unidentified disease, affecting dairy cattle in the Netherlands and Germany, Figure 11.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than monitoring the number of test requests, they were based on the assumption that the introduction of novel diseases will result in an increase in the number of samples that are not positive for the test requested by the veterinarian 54 , 55 or that do not reach a diagnosis for any disease after reasonable testing. 53 , 57 O’Sullivan et al 54 , 55 demonstrated a positive association between the volume of submissions of porcine reproductive and respiratory syndrome virus tests and the occurrence of a porcine circovirus-associated disease (PCVAD) outbreak, 54 as well as an increase in the proportion of negative tests, 55 confirming that such data sources can also contribute to the knowledge of new and existing disease patterns in the population.…”
Section: Overview Of Ahsys Initiatives and Methodological Developmentmentioning
confidence: 91%
“…Perrin et al 66 , 67 introduced an approach for mortality based on the use of movement data to calculate the population at risk and monitor mortality as a rate rather than counts. Negative laboratory results can also be monitored as proportions, 53 55 , 57 while rates were used by Marceau et al 10 , 94 and Bronner et al 14 for their reproduction indicators.…”
Section: Overview Of Ahsys Initiatives and Methodological Developmentmentioning
confidence: 99%
“…Animal data likely violated the assumptions required for the algorithms (Table 1). Animal surveillance data (especially diagnostic data) are influenced by changing economic circumstances within the livestock industry, such as large outbreaks [18], with outbreaks potentially affecting independence as well as denominators (see Table 1). Further, while animal samples submitted for routine surveillance and monitoring to comply with various legislative or industry requirements (e.g.…”
Section: Discussionmentioning
confidence: 99%